Comparison of early osseointegration of non-thermal atmospheric plasma-functionalized/ SLActive titanium implant surfaces in beagle dogs - Long, Li; Zhang, Min; Gan, Shuaiqi; Zheng, Zheng; He, Yanjin; Xu, Jia; Fu, Ruijie; Guo, Qiang; Yu, Deping; Chen, Wenchuan (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Hydrophilic dental implants are gaining increasing interest for their ability to accelerate bone formation. However, commercially available hydrophilic implants, such as SLActive™, have some major limitations due to their time-dependent biological aging and lower cost-effectiveness. The non-thermal atmospheric plasma (NTAP) treatment is a reliable way to gain a hydrophilic surface and enhance osseointegration. However, a few studies have been carried out to compare the osseointegration of NTAP-functionalized titanium implants and commercially available hydrophilic implants. Purpose: In this study, we compare the osseointegration abilities of the NTAP-functionalized titanium implant and Straumann SLActive. Material and methods: The NTAP effectiveness was examined using in vitro cell experiments. Then, six beagle dogs were included in the in vivo experiment. Straumann SLActive implants, SLA implants, and SLA implants treated with NTAP were implanted in the mandibular premolar area of dogs. After 2 w, 4 w, and 8 w, the animals were sacrificed and specimens were collected. Radiographic and histological analyses were used to measure osseointegration. Results: NTAP treatment accelerated the initial attachment and differentiation of MC3T3-E1 cells. In the in vivo experiment, bone parameters (e.g., BIC value and BV/TV) and volume of new bone of NTAP groups were close to those of the SLActive group. Additionally, although there was no statistical difference, the osseointegration of SLActive and NTAP groups was evidently superior to that of the SLA group. Conclusion: NTAP-functionalized implants enhanced cell interaction with material and subsequent bone formation. The osseointegration of the NTAP-functionalized implant was comparable to that of the SLActive implant at the early osseointegration stage.